AN EVALUATION OF ENGLISH TEACHERS IN MANAGING ONLINE CLASSROOM - Astri Wahyu Dini; Raynesa Noor Emilia Sari; Eva Fitriani Syarifah (Universitas Muhammadiyah Prof. DR. HAMKA, 2021)
The spread of COVID-19 virus give significant impact to the world of education. To reduce the spread of the virus, the Ministry of Education and Culture in Indonesia adapt by keeping physical from each other and limiting activities outside by carrying out teaching and learning activities process with online classroom. Online classroom is course that conducted fully over the internet. This research aimed to know what are media used by the English teacher in teaching English using online classroom, and how the teacher managed the online classroom. This type of research was field research with qualitative approach. Data collection techniques in this study are interview and documentation. The result of the study shows that the teacher uses different media and management in online classroom environment. The media used by the teacher included Whatsapp, Google Classroom, Youtube, and Google Form. The teacher managing the online classroom by giving rules, discipline, keeping teacher-student relationship by giving short comment and emoticon, and motivating through giving motivational word and giving point to the student. Those media and management help the teachers in managing their online classroom. Keywords: English Teacher, Media in Online Classroom, Managing Online Classroom